In Situ Mg/Ca Measurements on Foraminifera: Comparison Between Laser Ablation Inductively Coupled Plasma Mass Spectrometry and Wavelength‐Dispersive X‐Ray Spectroscopy by Electron Probe Microanalyzer. (2nd February 2021) - Balestra, B.; Rose, T.; Fehrenbacher, J.; Knobelspiesse, K. D.; Huber, B. T.; Gooding, T.; Paytan, A.
Abstract: We present a comparison of two different techniques: Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA‐ICP‐MS) and wavelength‐dispersive X‐Ray Spectroscopy by electron probe microanalyzer (EPMA) for obtaining Mg/Ca ratios in individual foraminifera shells. The goal is to assess the use of EPMA as an alternative technique for Mg/Ca analyses of single foraminiferal calcite shells. Foraminifera obtained from sediments (benthic, Uvigerina spp.) and from plankton tows (planktonic, Orbulina universa ) were analyzed. All specimens were prepared in epoxy mounts and exposed in cross‐section such that multiple high‐resolution analyses could be completed on the shells using both techniques. We examined our data using statistical methods designed for the assessment and comparison of measurement techniques. In the case of Uvigerina, the mean difference for ratios obtained using EPMA and LA‐ICP‐MS is very small (−0.046 mmol mol −1 ) and scale independent. The Limits of Agreement ( LoA, the standard deviation of the bias plus the mean bias) is [−0.315, 0.223] mmol mol −1 . For samples with ratios lower than 13 mmol mol −1, we found a mean EPMA–LA‐ICP‐MS bias of −2.44 mmol mol −1 and a corresponding LoA of [−3.85, −1.04] mmol mol −1 . For ratios higher than 13 mmol mol −1, there appears to be a scale dependent bias, meaning that the EPMA measured ratios become progressively larger than those of LA‐ICP‐MS as the Mg/Ca ratio increases, so the mean bias and LoA metrics are not meaningful. Results indicate that it is possible to use EPMA to collect Mg/Ca data, if the ratios are lower than ∼13 mmol mol −1 . Plain Language Summary: Analysis of the chemical composition of individual foraminifers using different techniques is necessary to compare data obtained using different methods, to increase the user base of single foraminifer analyses, and to enhance understanding of past paleoceanographic and paleoclimate events. We present a comparison of two different techniques: Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA‐ICP‐MS) and wavelength‐dispersive X‐Ray Spectroscopy by electron probe microanalyzer (EPMA) for obtaining Mg/Ca ratios in individual foraminifera shells. The goal is to assess the use of EPMA as an alternative technique for Mg/Ca analyses of foraminiferal calcite shells. Data obtained using these methods for two different species of foraminifera, the benthic Uvigerina and the planktonic Orbulina were evaluated. To assess our data, we used a statistically robust analysis technique designed for paired assessment of different methodologies, the so‐called Bland‐Altman analysis (Altman & Bland, 1983, https://doi.org/10.2307/2987937 ; Bland & Altman, 1986, https://doi.org/10.1016/S0140-6736(86)90837-8 ; Bland & Altman, 1999, https://doi.org/10.1177/096228029900800204 ). The Bland‐Altman statistical analysis of the data indicate that both instruments can be utilized to retrieve Mg/Ca ratios if 13 mmol mol −1 is set as the upper limit for these methodologies. Key Points: Comparison of two different techniques: Laser Ablation Inductively Coupled Plasma Mass Spectrometry and electron probe microanalyzer (EPMA) for obtaining Mg/Ca ratios in individual foraminifera shells The goal is to assess the use of EPMA as an alternative technique for Mg/Ca analyses of foraminiferal calcite shells Results indicate that it is possible to use EPMA to collect Mg/Ca data, if the ratios are lower than ∼13 mmol mol −1